Pengaruh Keterampilan Menulis Huruf Arab Terhadap Kemampuan Siswa Dalam Membaca Al-Qur’an Pada Mata Pelajaran BTQ - Fauziah, Hapsah; Widiawati, Suryani (STAI Al-Musaddadiyah Garut, 2023)
Reading and writing are two fundamental skills that students must master during the learning process, especially in the BTQ (Baca Tulis Qur’an) subject. The primary issue addressed in this research is the impact of Arabic writing skills on students' ability to read the Qur'an in the BTQ subject for seventh-grade students at MTs Al-Ashdariyah, Pakenjeng Garut. The objectives of this study are to answer the following research questions: 1) How are the students' skills in writing Arabic letters in the BTQ subject in the seventh grade at MTs Al-Ashdariyah described? 2) How are the students' abilities in reading the Qur'an in the BTQ subject in the seventh grade at MTs Al-Ashdariyah described? 3) What is the impact of Arabic writing skills on students' ability to read the Qur'an in the BTQ subject in the seventh grade at MTs Al-Ashdariyah? This research employs a quantitative approach using the correlational method. Data collection techniques include observation, tests, and document studies. The data analysis is conducted through statistical analysis. The results of this study indicate that the average skill level in writing Arabic letters in the BTQ subject is 3.62, which falls within the interval of 3.01-4.00, categorized as